Multilingual human, social, economic and management sciences terminology list - Department of Arts and Culture (Department of Arts and Culture, 2017)
The Human, Social, Economic and Management Sciences Terminology project is one of the school projects initiated by the Department of Arts and Culture. The project was identified around 2002 and its focus was on the Outcome Based Education (OBE). The terms were harvested from the textbooks that were received from different book publishing companies like Kagiso publishers, Nasou Via Africa Limited, Maskew Miller Longman (MML), etc. The project has now been adapted to reflect the new changes introduced because of the shift done by the Department of Basic Education (DBE) from the National Curriculum Statement (NCS) to the current Curriculum and Assessment Policy Statement (CAPS). Although the name of the project is still reflected as HSEMS, the main focus has now shifted to terms that are mainly found in the Economic and Management Sciences domain. The NLS believes that this multilingual terminology list will be an invaluable source in the teaching and learning. This source of reference will also assist teachers and learners to enhance their understanding and use of core economic and Management Sciences concepts. The compilers of the corpus hope that the project will also help the general public to understand these concepts better as they are presented in all the 11 official languages of the Republic of South Africa. The terminology list will also be published electronically and in the Department of Arts and Culture website
Department of Arts and Culture: Republic of South Africa